SAT-258 Surprising Transformation of a Microprolactinoma to a Macroprolactinoma - Athonvarangkul, Diana (J Endocr Soc, 2020)
Background: Microprolactinomas are typically benign tumors that rarely become macroprolactinomas. We present a rare case of a microprolactinoma that, after discontinuation of dopamine agonist (DA) therapy, transformed into a macroprolactinoma over a period of 6 years.Clinical Case: A 16-year-old woman initially presented for evaluation of galactorrhea without menstrual irregularities and was found to have elevated prolactin (68 ng/ml, normal range: 0-20), and a 4 mm pituitary microadenoma on MRI imaging. The patient was otherwise asymptomatic and other pituitary hormone levels were normal. She was treated with DA therapy (cabergoline 0.50 mg/week) which normalized her PRL level and improved but did not completely resolve the galactorrhea. She was then lost to follow up for 6 years. During that time, she discontinued cabergoline, but was still able to conceive, delivering a healthy baby after 2 years and breastfed briefly. She re-presented to her gynecologist 4 years after delivery for galactorrhea and secondary amenorrhea, both persistent since childbirth. Re-evaluation at that time revealed a much higher PRL level (432 ng/ml) and significant interval growth of the previous microadenoma to a 2.6 cm macroadenoma, now with extension into the left cavernous sinus, suprasellar cistern, with mass effect on the optic chiasm. The patient was retreated with cabergoline up to 3 mg/week, with a near-normal PRL level being achieved at 9 months (28 ng/ml). Repeat MRI revealed modest decrease of the adenoma to 2.4 cm. Galactorrhea resolved with reduction in PRL. However, amenorrhea persisted. Estradiol (30 pg/mL, 19-357 pg/mL) was low normal with normal withdrawal bleeding to medroxyprogesterone (MPA) challenge indicating reasonable estrogenization. She was treated with MPA to achieve regular cyclic bleeding every 3 months. Conclusion: This is an unusual case demonstrating significant growth of a microprolactinoma, which is typically a stable/indolent neoplasm, to a macroprolactinoma with invasive features. Previous studies of untreated microprolactinomas have shown that they undergo only subtle to minimal growth over 3 to 6 years and none transformed to a macroprolactinoma despite significant rises in PRL levels. In this clinical case, given the 6 intervening years that had elapsed in between MRIs, we cannot determine whether this represented moderate, progressive growth during that period after the discontinuation of DA therapy or whether the tumor had grown during pregnancy with its known stimulatory effects from hyperestrogenemia. The patient will require close follow-up to ensure ongoing shrinkage or at least stability of the adenoma and ongoing control of her hyperprolactinemia.References:1. Fertility and sterility39, 753-760 (1983). 2. Dietemann, J.L et al. Neuroradiology25, 133-138 (1983). 3. Garcia, M.M et al. Journal of endocrinological investigation18, 450-455 (1995).